Assessment of users’ behavior in Lithuanian online communities - Skarzauskiene, Aelita; Mačiulienė, Monika (Frontiers in Psychology, 2023)
Online communities are gaining importance in modern society by actively structuring public opinion and initiating discussions about various socio-economical issues. As information and communication technologies advance, the online communities are confronted with novel technological and societal hurdles (e.g., the spread of misinformation, lack of active participation). To boost their efficacy and productivity, it's crucial to enhance our understanding of user behaviour, communication avenues and potential future trends of development. There is a need to recognize online communities not as static entities, but as dynamic, evolving systems of collective intelligence. Online platforms serve a function beyond simply sharing information or knowledge; they act as influential social networks impacting various societal sectors, including politics, culture and the economy. Despite the multitude of challenges inherent to virtual communication, there remains a significant knowledge gap in comprehending general user behaviour within these online communities. Our study aims to bridge this gap by investigating user behaviour in Lithuanian online communities. By thoroughly analysing data gathered from a comprehensive quantitative study, we seek to raise awareness of the issues surrounding online communities, while also shedding light on social networking behaviour within these virtual spaces.